(untitled) (Annals of Medical Research, 2021)
Aim: The aim of this study is to compare the results of the patients for whom intracorporeal or extracorporeal anvil insertions were performed. Natural orifice specimen extraction (NOSE) surgery has been started from the 21st century onwards in order to reduce wound-related complications of laparoscopy. Two types of anvil placements, including intracorporeal or extracorporeal placements, are used in the application of NOSE, which is combined with distal colorectal surgery. Material and Methods: We retrospectively collected the data from 77 patients who underwent laparoscopic distal colorectal surgery combined with NOSE in our clinic between 2013 and 2019. Patients were evaluated in two groups as intra-corporeal and extracorporeal. Selection of the technique was based on the length of sigmoid colon and mesocolon. Demographic data, operative findings, pathological results and follow-up information were evaluated.Results: Of 77 patients who underwent distal colorectal surgery and circular stapler anastomosis; 44 were in the intracorporeal group and 33 were in the extracorporeal group. There was no difference between the two groups in terms of gender, age, BMI, comorbidity, and abdominal operation history of patients. The number of patients undergoing low anterior resection was higher in the extracorporeal group, and also the number of patients undergoing anterior resection was higher in the intracorporeal group. Peroperative findings, intraoperative and postoperative complications of patients were similar in both groups. The postoperative first-day pain scale was lower in the intracorporeal group (3.3±2.1 vs. 4.4±2.3, p=0.03). No significant difference was found between the two groups in other pain scales and cosmetic scores. The oncologic results were similar during the mean follow-up of 35.5±24.1 months.Conclusion: Although anvil placement techniques are not interchangeable, it is seen that neither method predominates the other in cases where both are suitable.